Expanding the phenotype of the CDKL5 deficiency disorder: Are seizures mandatory?. Issue 5 (8th February 2020) - MacKay, Conor I.; Bick, David; Prokop, Jeremy W.; Muñoz, Ivan; Rouse, John; Downs, Jenny; Leonard, Helen
Abstract: Pathogenic variants in the cyclin‐dependent kinase‐like 5 ( CDKL5 ) gene cause the neurodevelopmental disorder, the CDKL5 deficiency disorder. Reports of individuals with pathogenic variants in CDKL5 without seizures are exceedingly rare, and in‐depth analyses of their variants have been lacking. Whole‐genome sequencing was performed on a 29‐year‐old female with mild intellectual disability who, in the absence of overt seizures, presented with multiple episodes of altered mental status over a 24‐year period. Clinical history was supplemented by a parent completed questionnaire from the International CDKL5 Disorder Database. We identified a de novo heterozygous variant in CDKL5 (NM_003159.2:c.645T>A;p.Ser215Arg). In‐depth computational analysis performed to predict the impact of the variant on protein structure and function demonstrated that the variant was likely pathogenic. In this light, cell‐based studies showed that the S215R substitution causes a marked reduction in CDKL5 kinase activity. Similarities between our case and one previously reported case are striking. These cases, both without seizures but with apparent behavioral symptomatology, together question whether seizures are mandatory in this neurodevelopmental disorder.